Upgrading for overhead crane anti-sway method using variable frequency drive - Muhamad Nazri Omar; Mohd Muzafar Ismail; Mohd Nasir Ayob; Faiz Arith (Institute of Advanced Engineering and Science, 2022)
The paper discusses about upgrading the overhead crane anti-sway method base on the induction motor torque control from rotor resistance starter to variable frequency drives (VFDs). The upgrading included two phases. The phase 1 is to identify the performance of the overhead crane operation on anti-sway method base on the induction motor torque control using rotor resistance starter (old existing motor starter). The phase 2 is to identify the performance of the overhead crane operation on anti-sway method base on the induction motor torque control that use a variable of frequency drive (new upgrading motor starter). The primary equations connecting tractive force and load sway angle, which the motor torque control law is based on is designed for 0% load wobble at the end of the journey. The words accelerating and braking have been written. Outcomes of modelling the behaviour of a trolley-load of two masses for the normal overhead crane load ratios, a system is described weight to the length of the rope, which supports the hypothesis concerning the feasibility of direct load anti-sway control ON and OFF for regulation of motor for overhead cranes.